Following similar paths what American Jews and Muslims can learn from one another - Heilman, Samuel C. 1946- (University of California Press, 2024)
"Two academics, one Jewish and one Muslim, come together to show how much their faiths have in common--particularly in America. This book provides a braided portrait of two American groups whose strong religious attachments and powerful commitments to ritual observance are not always easy to adapt to American culture. Orthodox Jews and observant Muslims share many similarities in their efforts to be at home in America while holding on to their practices and beliefs. As Samuel Heilman and Mucahit Bilici reveal, they follow similar paths in their American experience. Heilman and Bilici immerse readers in three layers of discussion for each religious group: historical evolution, sociological transformation, and a comparative understanding of certain parallel beliefs and practices, each of which is used as a window onto the lived reality of these communities. Written by two sociologists, one a religiously observant American Jew and the other an American Muslim, Following Similar Paths offers lively insider and outsider perspectives that deepen our understanding of American diversity and what it means to be religious in a modern society."
Keywords: Interreligiöser Dialog; Muslim; Juden; USA; Jews / United States / Social conditions; Muslims / United States / Social conditions